Pengaruh Penilaian Tingkat Kesehatan Bank Terhadap Praktik Manajemen Laba Pada Bank Umum Syariah di Indonesia - Salma Cantya Paramastri; Radia Purbayati; Dimas Sumitra Danisworo (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
Earnings management is carried out to show that the company is in good condition even though in reality it is not good. These practices are not in accordance with sharia principles. This study aims to determine the effect of the Bank Soundness Level Assessment using the RGEC method on earnings management practices in Islamic Commercial Banks in Indonesia for the 2015-2018 period. The variables used are the Financing to Deposit Ratio (FDR), Return On Assets (ROA), Good Corporate Governance (GCG), and Capital Adequacy Ratio (CAR). Testing the variables using the Path Analysis method with a sample of 9 Islamic Commercial Banks in Indonesia. The results showed that the FDR and CAR variables had a negative and significant effect; ROA has a positive and insignificant effect; and GCG has a negative and insignificant effect on earnings management practices at Islamic Commercial Banks in Indonesia.